TEA v primerjavi s PTA pri zdravljenju stenoze karotidnih arterij - Šavli, Tomaž (Medicinski razgledi, 2009)
In the beginning of the century a new percutaneous metod has evolved in treatment of carotid artery stenosis as an alternative to the carotid endarterectomy. First trials showed promising results and inspired the "percutaneous enthusiasts even more. During the last years many trials comparing these two methods have been completed. Findings were controversial and the most important, they were all missing results over a longer period. These are now becoming more abundant, therefore so on it will be possible to make new conclusions, abstract guidelines in treatment of carotid artery ocludive disease etc. In this article we reviewed mostly meta-analyses and review articles addressing this issue. We can conclude that the described two methods are equally efficient, but also that the carotid endarterectomy stil! remains first-line treatment, mainly because of lower incidence of stroke and death in 30 days after procedure. Both methods have different characteristics,which we think, can be used in favor of the patients.
Keywords: Carotid Stenosis; Karotidna stenoza; Endarterektomija karotidna; Therapy; Angioplastika balonska; Angioplasty, Balloon; Endarterectomy, Carotid; Meta-analiza; Meta-Analysis; cardiovascular disease; kardiovaskularne bolezni; karotidne arterije; stenoza; zdravljenje; angioplastika; metode